Ultrasonic Pulsating Water Jet Peening: Influence of Pressure and Pattern Strategy - Stolárik, Gabriel; Nag, Akash; Petrů, Jana; Svobodová, Jaroslava; Hloch, Sergej (Materials (Basel, Switzerland), 2021)
Peening techniques are nowadays attracting more research attention due to their association with the extending of the service life and improving surface texture of engineering components. Ultrasonic pulsating water jet peening represents a new way of mechanical surface treatment. Accelerated water droplets via hammer effect cause small elastic-plastic deformations on the surface. This work deals with peening of aluminum alloy using an ultrasonic pulsating water jet, where periodically acting water droplets were used as the peening medium. The aim of the work was the feasibility study of the peening process and to observe the effects of pressure (p = 10, 20 and 30 MPa) and pattern trajectory (linear hatch and cross hatch). The peened surfaces were analyzed by the surface roughness profile parameters Ra and Rz and the microhardness along the peening axis into the material. Graphically processed results show a clear increase of measured values with increasing pressure (p = 10, 20 and 30 MPa), where the roughness values ranged from 1.89 µm to 4.11 µm, and the microhardness values ranged from 43.3 HV0.005 to 47 HV0.005, as compared to 40.3 HV0.005 obtained for the untreated sample. The achieved results indicate potential using of an ultrasonic pulsating water jet as a new method of surface treatment of metals. By controlled distribution of water droplets, it is possible to achieve a local distribution of surface roughness, and at the same time, strengthening of the subsurface layers in the material without thermal influence on the material.
Keywords: surface topography; surface modification; PWJ peening; microhardness